Cooling Machine Adapted Peltier Cooling Module TEC1-12706 to Understand Heat Transfer Application - Mardiansah suares, Reza; Maulana, Ivan; Ikhsanudin, Zaky; Imam Ghozali, Achmad; DwiYanto, Agus; abyan H, Rakha; Robi F, Achmad; Setiawan Y, Mazadi; Radissa Dzaky Issafira; Wiliandi Saputro (BIOMEJ, 2024)
This paper discusses the development of a simple refrigeration system that utilizes a PSU (Power Supply Unit), Peltier TEC1-12706 module, axial fan, and heatsink. This system is designed to provide an efficient solution for cooling limited spaces or electronic devices at an affordable cost. The PSU is used as the main electrical power source, while the Peltier module functions as the main cooling element that utilizes the thermoelectric effect. An axial fan is integrated to improve heat transfer, increase cooling efficiency, and maintain operational temperatures at desired levels. Heatsinks are used as an addition to the heat absorption and distribution process, ensuring optimal system performance. This research involves experimental testing to measure the system's ability to reduce temperatures and maintain operational stability. The experimental results show that data was obtained from the 5th minute to the 30th minute. The average temperature was 18.54˚C in the 5th minute, 16˚C in the 10th minute, 14.88˚C in the 15th minute, 14.88˚C in the 10th minute. in the 20th minute it was 14.34˚C, in the 25th minute it was 14˚C, and in the 30th minute it was 13.78˚C and obtained a maximum COP value of 0.702 and actual COP 0.212. This research contributes to the development of efficient and affordable cooling technology by utilizing components that are easy to access and apply.